Bioenergy and agriculture: Promises and challenges: Potential of carbon payments for bioenergy - Knudsen, Odin (International Food Policy Research Institute, 2006)
Agriculture around the world is already mitigating climate change through the increased growing of crops and trees. But much more can be done to bring agriculture into the center of climate change mitigation and to encourage a greater role for sustainable bioenergy production. The result could be not only a better global environment, but increased revenues for farmers, more energy self-suff iciency for rural communities, and preservation of natural forests and biodiversity. Through the Kyoto Protocol, the world community moved toward realizing the potential of agriculture for mitigating climate change, but not enough to gain the full benefits. If the world community can rally around the potential of agriculture and forest management in combating climate change and provide an international regulatory structure that permits this potential to be realized, the benefits to the world’s climate and poverty reduction in developing countries could be enormous, perhaps even exceeding the benefits of trade in agricultural products and development aid. These steps would also enable carbon payments to be harnessed for the development of sustainable bioenergy production.